2022
DOI: 10.1111/een.13184
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of a method used to study nutritional effects on bumble bees

Abstract: Bee declines are an increasingly recognised problem globally. Nutritional stress due to agricultural intensification is one of the drivers of bee declines. Therefore, understanding the nutritional requirements of bees is crucial to mitigate the effects of food scarcity on bee populations. Laboratory studies evaluating nutritional effects on bumble bees often use microcolonies as a model system for effects on queenright colonies. Microcolonies consist of workers, whereby one worker will lay male‐destined unfert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The workers with higher protein had higher productivity, and the drones were heavier [ 34 ]. In another study, a queenright B. terrestris colony was fed pollens containing 22%, 18%, and 14% crude protein; the results showed that the pollen group with 22% protein content had lower larval mortality and heavier weighted workers than the pollen group with 14% protein content [ 35 ]. In our study, combined with the reproduction performance and pollen nutrition, the results show that the higher crude protein and essential amino acid contents in the camellia pollen mix can contribute to the strong performance of B. breviceps queens and colonies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The workers with higher protein had higher productivity, and the drones were heavier [ 34 ]. In another study, a queenright B. terrestris colony was fed pollens containing 22%, 18%, and 14% crude protein; the results showed that the pollen group with 22% protein content had lower larval mortality and heavier weighted workers than the pollen group with 14% protein content [ 35 ]. In our study, combined with the reproduction performance and pollen nutrition, the results show that the higher crude protein and essential amino acid contents in the camellia pollen mix can contribute to the strong performance of B. breviceps queens and colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to some research results, our results suggest that it took a shorter amount of time for the colony to reach ten workers under the camellia pollen mix and camellia–oilseed rape–apricot pollen mix, with higher protein contents. Wynants et al reported that protein contents of 21.8%, 21.4%, 18.4%, and 11.9% were fed to a queenright B. terrestris colony, and they found that the number of offspring with a higher protein content increased faster [ 35 ]. This may be because when the first worker emerges successfully, it can continue to feed on pollen with high protein and essential amino acid contents, which allows the worker’s body size to develop faster, and helps the queen to brood, thus reducing the time required for the colony to reach ten workers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations